On the taxonomy of Afrotropical Coleophoridae (III). New or little known species from Central and Oriental Africa (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio; van Der Wolf, Hugo W. (Zootaxa, 2020)
This work presents a review of the Coleophoridae of Central and Eastern Africa. A lectotype is designated for Coleophora psychropa Meyrick, 1920, and the male genitalia of C. crossanthes Meyrick, 1938, are illustrated for the first time. Coleophora sabaea Baldizzone, 2007, previously known only from Yemen, is added to the African fauna. Nine new species of Coleophora Hübner, 1822 are described: C. schouteni sp. nov., C. giustii, sp. nov., C. centrafricana sp. nov., C. riftella sp. nov., C. camerunensis sp. nov., C. ensifera sp. nov., C. gilgilensis sp. nov., C. nyanzaensis sp. nov., C. silvestris sp. nov.